ANALISIS KINERJA FILTRASI ARANG DAN IJUK PADA INSTALASI PEMANENAN AIR HUJAN (IPAH) KOMUNAL SEBAGAI UPAYA PENINGKATAN AKSES AIR BERSIH DI DESA TIHINGAN, KABUPATEN KLUNGKUNG, BALI - Febryan Aristarchus Rajagukguk; Ida Bagus Made Baskara Andika; Cokorda Istri Niti Laksmi Dewi; Rahma Swari Ramadhani; Fanni Ibrahim Sholeh Siregar; Michael Hesy Kurnia (Jurnal Spektran, 2025)
The decline of green open space and uneven water distribution resulted in limited access to clean water in Tihingan Village, Banjarangkan District, Klungkung Regency. This condition poses challenges for fulfilling the community’s basic needs for consumption and hygiene-sanitation. Communal Rainwater Harvesting Installation (Instalasi Pemanenan Air Hujan/IPAH) is proposed as a strategic alternative of appropriate technology in clean water provision. Raw rainwater often does not meet clean water standards, thus requiring an effective and affordable filtration process. This study aims to analyze the performance of charcoal and palm fiber filtration media in improving the quality of harvested rainwater in communal IPAH to meet Class I clean water standards. A descriptive-comparative method with an experimental laboratory approach was employed. Rainwater samples were collected before (influent) and after filtration (effluent). Tested parameters included pH, Escherichia coli content, Total Suspended Solids (TSS), and ammonia (NH₃). The filtration media consisted of a combination of locally sourced charcoal and palm fiber. Results showed that the filtration effectively reduced TSS, decreased E. coli content to meet quality standards, and lowered ammonia to safe levels, with improved pH levels. The water quality after filtration complied with Class I clean water standards and was suitable for hygiene and sanitation purposes. This system proved effective, inexpensive, environmentally friendly, and supported sustainable clean water provision while providing local economic benefits. Filtration using charcoal and palm fiber media can be a practical and replicable model to provide clean water in similar regions.